SELF-STRUCTURED SILVER ALLOY COATINGS AND THEIR PROPERTIES - Krastev, I. (Journal of Engineering & Processing Management, 2009)
The co-deposition of silver with less noble metals results at low current densities in pure silver coatings or solid solutions of these metals in silver. At high current densities, after saturation of the silver lattice with the alloying metal a new richer in this element phase is formed and heterogeneous coatings are obtained. The spontaneous deposition of different phases is sometimes connected with electrochemical instabilities and oscillation phenomena leading to formation of periodically ordered spatio-temporal structures on the surface of the electrode. The spreading of waves of different metal composition over the electrode could result in the spontaneous formation of multilayered coatings, which combine the properties of the phases of the different sublayer. The possibility of spontaneous formation of heterogeneous periodic self-structured coatings in microand nano-scale, based on silver alloys with antimony, bismuth, indium, tin, cadmium and other metals without applying external pulses is shown. The effect of electrolysis conditions on the morphology, internal stress, microhardness, electrical contact resistance, wear resistance, roughness and friction properties of the obtained alloy coatings is studied and some properties of the deposited layers are compared and discussed.